Effect of dietary intervention with different pre- and probiotics on intestinal bacterial enzyme activities - Preter, V. de; Raemen, H; Cloetens, L; Houben, E; Rutgeerts, P; Verbeke, K (European journal of clinical nutrition, 2008)
Objective: To investigate the influence of different pre- and probiotics on faecal β-glucuronidase and β-glucosidase activity, as one of the claimed beneficial effects of pre- and probiotics is the hypothesis that these substrates are able to reduce the production of toxic and carcinogenic metabolites by suppressing specific enzyme activities in the colon. Setting: Department of Gastrointestinal Research, University Hospital Gasthuisberg, KU Leuven, Belgium. Design and subjects: The effect was evaluated in a randomized, crossover study in 53 healthy volunteers who were randomly assigned to one of five treatment groups. Interventions: At the start and after a 4-week treatment period, the healthy volunteers collected faeces during 72 h. Lactulose and oligofructose-enriched inulin (OF-IN) were chosen as prebiotics, whereas Lactobacillus casei Shirota, Bifidobacterium breve and Saccharomyces boulardii were selected as probiotics. Two synbiotic combinations were evaluated as well. The enzyme activity was assessed spectrophotometricly. Results: Lactulose and OF-IN significantly decreased β-glucuronidase activity, whereas a tendency to a decreased β-glucuronidase activity was observed after L. casei Shirota and B. breve intake. To the contrary, B. breve increased β-glucosidase levels. Supplementation with the synbiotic did not appear to be more beneficial than either compound alone. No influence of S. boulardii was noted. Conclusions: Administration of lactulose, OF-IN, L. casei Shirota or B. breve resulted in a decrease of the β-glucuronidase activity, which is considered beneficial for the host.